2016
DOI: 10.1007/s10035-016-0632-2
|View full text |Cite
|
Sign up to set email alerts
|

Macro deformation and micro structure of 3D granular assemblies subjected to rotation of principal stress axes

Abstract: This paper presents a numerical investigation on the behavior of three dimensional granular materials during continuous rotation of principal stress axes using the discrete element method. A dense specimen has been prepared as a representative element using the deposition method and subjected to stress rotation at different deviatoric stress levels. Significant plastic deformation has been observed despite that the principal stresses are kept constant. This contradicts the classical plasticity theory, but is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 31 publications
(57 reference statements)
2
22
0
Order By: Relevance
“…There are three main methods for imposing boundary conditions in DEM simulations: (1) rigid wall, (2) periodic boundary, and (3) flexible boundary. Rigid walls are the most widely used type of boundary . Li and Yu performed two‐dimensional DEM simulations of PSR with polygon samples enclosed by rigid walls.…”
Section: Dem Simulation Methods For Psr In Different Planesmentioning
confidence: 99%
See 3 more Smart Citations
“…There are three main methods for imposing boundary conditions in DEM simulations: (1) rigid wall, (2) periodic boundary, and (3) flexible boundary. Rigid walls are the most widely used type of boundary . Li and Yu performed two‐dimensional DEM simulations of PSR with polygon samples enclosed by rigid walls.…”
Section: Dem Simulation Methods For Psr In Different Planesmentioning
confidence: 99%
“…Smaller initial density, larger stress ratio q / p , larger mean stress p , and larger intermediate principal stress ratio b all result in larger volume contraction in drained PSR tests. Noncoaxiality between the major principal directions of the stress tensor and the (plastic) deviatoric strain increment tensor is observed, while the classical theory of elasto‐plasticity gives coaxiality of stress and plastic strain increments. The macroscopic noncoaxiality is considered to originate from the evolution of fabric anisotropy and internal structures .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rotational cyclic loading has been a typical non-proportional test, widely encountered in soils during earthquake and offshore/coastal wave loads, and has been proven difficult to model within a continuum mechanical framework. Li et al [28] carried out 3D DEM simulations to examine the relation between deformation and fabric structure for a dense assembly subjected to a continuous rotation of the (applied) principal stress direction. Using the contact-based fabric tensor, they found that the rotation of the principle stress axes led to densification of their samples with greater coordination numbers and cyclically varying fabric anisotropy, as also reported by Kumar et al [17].…”
Section: Signatures Of Fabric and Fabric Evolutionmentioning
confidence: 99%